NATIONAL SECURITY CONCEPT - Daniel DUMITRU (Annals: Series on Military Sciences, 2018)
The paper is the result of scientific research on the evolution of the concept of security (national security). The paper/article highlights: the stages of the evolution of the national security concept; security definitions and national security; the components of national security.